Sites of Memory and Exchanges of Places (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article focuses on the exchange of places between the authentic sites where extermination itself happened during the Holocaust and the development, all over the world, of new sites to commemorate the memory of the victims. As well as, it looks into a paradox that occurs between the diffi- culties for transmission the event and the excess of insti- tutions and memorials. Finally, it examines if art, cinema, literature, the contra-monumento and happening are able response to a world in which the memorial will be replaced by a posmemoria
Keywords: Holocaust; Mundialization; Sites of Memory; Transmission.